Islam Nusantara: A Semantic and Symbolic Analysis - Woodward, Mark (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2017)
This paper presents semantic and symbolic analyzes of the concept of Islam Nusantara and how it evokes meaning and emotion to counter extremist and violent transnational movements, including al-Qaeda and ISIS, based on the Salafi-Wahhabi ideology. The paper is based on a religious, cultural, and political theme framework in two films produced by Nahdlatul Ulama (NU): The Blessing of Islam Nation (Oceans of Revelation: Islam as a Blessing for All Creation) and Launching the Film The Blessing Islam Nusantara. The first is based on elements of Sufism, Javanese and some other Indonesian cultures to build a vision of Islam which directly opposes the hard and non-violent Salafi-Wahhabi extremist. The latter promoted the film and the potential of the Ansor (NU) youth organization to combat extremism and terrorism. Theoretically, I rely on the insight by Goffman's observations of "framing" and "reframing" and Sperber's demonstration that symbolization is one of the cognitive processes that awaken and simultaneously communicate meaning and emotion.